Compulsory licensing under South Africa's National Water Act. Issue 6 (18th September 2016) - Kidd, Michael
ABSTRACT: This article considers the statutory scheme for compulsory licensing in South Africa and examines its use in three case studies. Their evaluation reveals the complexity and time-consuming nature of the process. This, coupled with other challenges, particularly in relation to the achievement of equity (redress), is likely to result in the slow achievement of the National Water Act's objectives through compulsory licensing. There are no realistic alternatives to licensing if the constitutionally required goal of equity is to remain critical.